PENGARUH BAURAN RITEL TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN PADA PAMELLA SWALAYAN YOGYAKARTA.pdf - Muhammad Salman Al Farisi (Jurnal Manajemen Bisnis dan Keuangan, 2020)
Customer satisfaction which creates loyalty is an important factor in the success ofthe retail trade and retail stores ability to survive. In today's era of the modern market, loyaltycan be determined directly by the customer expectations of products and services offered, oralso by the application of a set of retail marketing mix. The goal of this research is to knowthe direct effect of retail marketing mix strategy which consist of product, price, place,personality, and presentation on customer satisfaction of Pamella Swalayan and to know andanalize the effect of customer satisfaction on customer loyalty. This reseach is quantitativeresearch. Population on this research is all of Pamella Swalayan’s customers. Sampling setmethod is using purposive sampling technic with criteria doing purchase transaction at leasttwo times a month. Calculation of sampling is using Slovin formula so that obtained 100samples.The theory used in this research is primary and secondary theory. The method ofdata collection is by fill the questionnaires with using Likert scale while the secontary dataobtained by documentation study. The technic of analysis is descriptive and quantitativeanalysis. First hypotesis test is using multiple linear regression analysis and the secondhypotesis test is using simple linear regression. The result of this research shows thatsimultaneously product, price, place, personality, and presentation have a positive andsignificant influences to customer satisfaction in Pamella Swalayan. Partial test shows thatproduct, place, personality, and presentation have a positive and significant influence tocustomer satisfaction . while price in unsignificant effect with customer satisfaction. Theresult of this research also shows that customer satisfaction have a positive and significantinfluences to customer loyalty. From this research we can know that customer satisfaction isthe most dominant factor that effect to customer loyalty.